Imperial Babel : Translation, Exoticism, and the Long Nineteenth Century - Rangarajan, Padma (Book collections on Project MUSE., 2014)
"Imperial Babel: Translation, Colonialism, and the Long Nineteenth Century, examines the complex and largely ignored history of translation in the British Empire. Challenging common assumptions that the production of orientalist translations was inescapably coercive and unidirectional, Imperial Babel demonstrates the tenuous and often collaborative nature of imperial knowledge-production by studying the real translative policies of Empire, and the ways in which literary adaptors of translations and translators themselves resisted and reified imperial and cultural sovereignty"--